Future Identity as a Support for College Motivation and Success - Destin, Mesmin; Silverman, David M.; Braslow, Matthew D. (Frontiers in Education, 2022)
Many postsecondary education institutions in the United States struggle to effectively support high levels of academic achievement and college completion among their students. This is especially true at less selective and online colleges and universities that are understudied but serve an increasing number of students. Psychological factors may play an important role in promoting positive student outcomes during the college years. Two randomized controlled experiments including online university students focused on the potential influence of opportunities for students to reflect upon their future identities or ideas about their lives in the years to come. In Study 1 (N = 1,042), a course activity designed to engage students’ future identities showed positive effects on course grades and persistence in college during the next semester. In Study 2 (N = 2,515), a more rigorous design demonstrated the effects of activating future identities on specific motivational processes with positive consequences for academic outcomes. Together, the experiments suggest that educators and advisors should engage with how students imagine their futures in order to help support student success.